2015
DOI: 10.1007/s10792-015-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the retinal ganglion cell and choroidal thickness in young Turkish adults with hyperopic anisometropic amblyopia

Abstract: The purpose of this study is to compare the choroidal thickness (CT) and ganglion cell complex (GCC) thickness of the normal fellow eyes and the amblyopic eyes using enhanced depth imaging optical coherence tomography (EDI-OCT) in young Turkish adults with hyperopic anisometropic amblyopia. Patients with unilateral hyperopic anisometropic amblyopia were enrolled and underwent a full ophthalmological assessment, including best-corrected visual acuity, cycloplegic refraction, and axial length (AL) measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
16
2
Order By: Relevance
“…In adults with anisometropic amblyopia, there was no significant difference in the subfoveal choroidal thickness between amblyopic and fellow or control eyes. [ 17 , 18 ] In children, the choroid may have greater flexibility compared to that in adults. We found that amblyopic eyes had larger luminal areas than that of normal children.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with anisometropic amblyopia, there was no significant difference in the subfoveal choroidal thickness between amblyopic and fellow or control eyes. [ 17 , 18 ] In children, the choroid may have greater flexibility compared to that in adults. We found that amblyopic eyes had larger luminal areas than that of normal children.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have recently used SD-OCT to assess the thickness of the retina [ 11 ] or choroid [ 13 , 16 22 ] in unilateral amblyopia. However, none of the previous reports have used SS-OCT to analyze the retinal and choroidal thickness at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the previous reports have used SS-OCT to analyze the retinal and choroidal thickness at the same time. Furthermore, these previous studies manually performed the choroidal thickness measurements only at specific points and not over defined areas [ 13 , 16 22 ]. Thus, the current study is the first to use SS-OCT to evaluate the averaged regional retinal and choroidal thickness in unilateral amblyopia using a 3D map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read the article entitled as ''Evaluation of the retinal ganglion cell and choroidal thickness in young Turkish adults with hyperopic anisometropic amblyopia'' by Celik et al [1] with great interest. The authors investigated the choroidal thickness (CT) and ganglion cell complex (GCC) thickness of the normal fellow eyes and the amblyopic eyes using enhanced depth imaging optical coherence tomography (EDI-OCT) in 43 young Turkish adults with hyperopic anisometropic amblyopia.…”
Section: Dear Editormentioning
confidence: 99%